2008
DOI: 10.1097/ede.0b013e318187a7b0
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported and Measured Sleep Duration

Abstract: Recent epidemiologic studies have found that sleep duration is associated with obesity, diabetes, hypertension and mortality. These studies have used self-reported habitual sleep duration, which has not been well validated. We model the extent to which self-reported habitual sleep reflects average objectively measured sleep. Eligible participants at the Chicago site of Coronary Artery Risk Development in Young Adults Study were invited to participate in a 2003-2004 ancillary sleep study; 82% (n=669) agreed. Sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
886
7
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,331 publications
(946 citation statements)
references
References 42 publications
47
886
7
6
Order By: Relevance
“…An analysis of 669 participants in the CARDIA (Coronary Artery Risk Development in Young Adults) Sleep Study suggests a moderate correlation between self‐reported and objectively measured sleep duration with evidence of systematic errors in the mean and calibration 97. Another study of 2086 Hispanic Americans suggests a moderate correlation between self‐reported sleep and actigraphy results 98.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of 669 participants in the CARDIA (Coronary Artery Risk Development in Young Adults) Sleep Study suggests a moderate correlation between self‐reported and objectively measured sleep duration with evidence of systematic errors in the mean and calibration 97. Another study of 2086 Hispanic Americans suggests a moderate correlation between self‐reported sleep and actigraphy results 98.…”
Section: Discussionmentioning
confidence: 99%
“…First, information about sleep duration was self-reported by the parents of the participants. Although good correlations between objectively measured and the self-reported durations in children have been observed, 39,40 this may still compromise the accuracy of the study. Second, there were very few 5 to 10-year-olds in our study who slept at least 11 hours and there were few 15 to 18-year-olds overall, thus yielding a limited statistical power to test the association between sleep duration and hypertension in these subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study was limited by the use of crosssectional data, which do not allow for causation to be determined, and self-report measures, which are not always accurate or reliable. Lauderdale et al (2008), for example, found that self-reported sleep duration correlated modestly with objectively measured sleep duration and was affected by factors such as race, education, income and health status. Therefore, some relationships observed in this paper could reflect an inability for some groups of people to accurately assess their sleep duration.…”
Section: Study Limitations and Strengthsmentioning
confidence: 99%